2017
DOI: 10.1021/acssuschemeng.7b01041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Pathogenic Cleanup of Wastewater Using Surface-Functionalized CeO2 Nanoparticles

Abstract: In this paper, we report the simple synthesis, detailed characterization, and total wastewater cleanup by adsorption using bare and surfactant-functionalized cerium oxide (CeO 2 ) nanoparticles. The synthesis of CeO 2 nanoparticles was performed by a facile aqueous solution process and characterized by a diverse range of techniques, which confirmed that the nanoparticles are well-crystalline, possessing good structural and optical properties. The competence of the prepared nanoparticles was further explored to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…34−36 In addition, surface functionalization and modification were adopted to enhance the activities of oxides. 37,38 Although CeO 2 -based materials have gained increasing attention as alternative photocatalysts to the more conventional TiO 2 -based materials, there is limited information regarding the application of other types of cerium-based materials for the removal of dye contaminants from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…34−36 In addition, surface functionalization and modification were adopted to enhance the activities of oxides. 37,38 Although CeO 2 -based materials have gained increasing attention as alternative photocatalysts to the more conventional TiO 2 -based materials, there is limited information regarding the application of other types of cerium-based materials for the removal of dye contaminants from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure 1, a sharp and strong peak appears in the 509 and 560 cm À1 in the CeO 2 nanoparticles prepared at 500 and 600 C, respectively, which indicates the bond vibration of Ce-O. [4,7,53,55,57,59] Also, the two broad and weak peaks in the 1,620 and 3,485 cm À1 are related to the vibrations of water molecules absorbed by the CeO 2 nanoparticles. [3,7] The peak of impurities is not seen in these spectra.…”
Section: Characterizationmentioning
confidence: 94%
“…[7][8][9]11,12,19] Cerium oxide nanoparticles [39,44] used as supercapacitor, [48] solar cell, [49] cytotoxic activity, [50] photodynamic therapy, [51] biomedical application, [52] also as photocatalytic degradation of organic pollutants [1][2][3][4][5][6] and different organic dyes. [7][8][9][53][54][55][56][57][58][59][60][61][62] The main purpose of this paper is to prepare cerium oxide (CeO 2 ) nanoparticles via solution combustion technique and use them for photocatalytic degradation and removal of methylene blue dye.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, after the inoculum size 2.5% for T. fasciculatum and 2.0% for T. longibrachiatum, the uptake and percentage removal of the Cd 2+ ions were decreased significantly. It has been reported that the percentage removal of heavy metal ions increases with enhancing the adsorbent dose due to the fact that it increases the adsorption sites, which leads to high adsorption and high removal efficiency [42][43][44].…”
Section: Inoculum Size Effectmentioning
confidence: 99%